Prosthetic arm Controller Based on Brainwaves Spectrum EEG Sensor - Utama, J; Palada, G (IOP conference series. Materials Science and Engineering, 2019)
The purpose of this study is to discuss the brain wave system that can move the prosthetic arm based on brain wave activity. The sensor used to detect EEG brainwave activity uses a mobile mind wave sensor. Movement and detection of brainwave signals is carried out in the Lab VIEW application program. Plan this robot to make movements based on brain wave activity, utilizing blinks and attention. This research method through a process carried out to control the prosthetic arm. Where there are 2 modes, the first mode for the selection of movements with a blink of an eye, and the second mode of attention to move the fake arm. Based on research results Prosthetic arms can make movements that are designed for extension, flexion, supination or pronation and increase or depression. The prosthetic arm can make movements based on the subject's commands by utilizing brain wave activity. With a speed response time of 9.54 seconds to do all the moves. In addition to the advantages of this artificial arm, it can accommodate objects with a diameter of 2.2 cm to 6 cm. With an average percentage success of 6 experiments conducted by 86.67%.